Analisis Tindak Tutur Ilokusi Pada Video Pembelajaran Pidato Bahasa Indonesia Dalam Kanal Youtube “Literasi Untuk Indonesia” - Amrina Rosyada; Aminatul Fitroh; Erina Hidayah; Nurul Lisa Kusumaningrum; Salma Dian Ramadhan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Currently, many learning videos are available on various social media platforms. It is hoped that each video will achieve existing learning objectives and enable students to understand and implement the results of their learning activities well. This research aims to examine and explain the types and forms of illocutionary speech acts found in several learning videos and evaluate whether the speech acts in these videos support the development of Indonesian language literacy and speaking skills in giving speeches. Illocutionary speech acts relate to the power effect obtained by the audience of an utterance uttered by the speaker. This research article uses a theoretical approach, namely a pragmatic approach with an analysis of the types and forms of illocutionary speech acts. In this research, qualitative descriptive methods were used to analyze related data. Data was obtained from six speech learning videos on the YouTube channel, and the data collection technique involved proficient free-involved listening (SBLC) and note-taking techniques. Researchers watched videos about learning speech texts on the Literacy for Indonesia YouTube Channel, then took notes and recorded utterances that contained illocutionary utterances. The data analysis technique uses matching and high techniques to study the form and type of illocutionary speech. From the data analysis that has been carried out, it was found that there are assertive utterances giving testimony and stating, directive utterances giving advice and ordering, expressive utterances containing prayers and hopes, and commissive utterances offering and promising. It is hoped that the results of the analysis in this article will increase deeper understanding and knowledge regarding illocutionary speech acts and their use, knowledge about their types, as well as guide educators and online learning material creators to increase learning effectiveness.